The natural compound silvestrol inhibits hepatitis E virus (HEV) replication in vitro and in vivo - Todt, Daniel Matthias; Dao Thi, Viet Loan (Antiviral research, 2018)
Hepatitis E virus (HEV) is the causative agent of hepatitis E in humans and a member of the genus Orthohepevirus in the family Hepeviridae. HEV infections are the common cause of acute hepatitis but can also take chronic courses. Ribavirin is the treatment of choice for most patients and type I interferon (IFN) has been evaluated in a few infected transplantation patients in vivo. However, no effective and specific treatments against HEV infections are currently available. In this study, we evaluated the natural compound silvestrol, isolated from the plant Aglaia foveolata, and known for its specific inhibition of the DEAD-box RNA helicase eIF4A in state-of-the-art HEV experimental model systems. Silvestrol blocked HEV replication of different subgenomic replicons in a dose-dependent manner at low nanomolar concentrations and acted additive to ribavirin (RBV). In addition, HEV p6-based full length replication and production of infectious particles was reduced in the presence of silvestrol. A pangenotypic effect of the compound was further demonstrated with primary isolates from four different human genotypes in HEV infection experiments of hepatocyte-like cells derived from human embryonic and induced pluripotent stem cells. In vivo, HEV RNA levels rapidly declined in the feces of treated mice while no effect was observed in the vehicle treated control animals. In conclusion, silvestrol could be identified as pangenotypic HEV replication inhibitor in vitro with additive effect to RBV and further demonstrated high potency in vivo. The compound therefore may be considered in future treatment strategies of chronic hepatitis E in immunocompromised patients.